Pain in Guillain––Barréé syndrome. (March 2011) - Umapathi, Thirugnanam; Yuki, Nobuhiro
Evaluation of: Ruts L, Drenthen J, Jongen JL et al. Pain in Guillain––Barréé syndrome: a long-term follow-up study. Neurology 75, 1439––1447 (2010). Pain has been recognized as an important symptom of Guillain––Barréé syndrome (GBS). The article under review prospectively studied the phenomenon of pain in a cohort of 156 GBS patients for a period of 1 year. It confirmed that pain of significant intensity is relatively common in all subtypes of GBS. It may start before the onset of other symptoms. It correlates with sensory loss, severity of the GBS at its nadir and the presence of diarrhea. In the recovery/chronic stages it correlates with weakness, disability and fatigue. Up to a third of patients have pain at 1 year.